De novo transcriptome based insights into secondary metabolite biosynthesis in Malaxis acuminata (Jeevak)–A therapeutically important orchid - Bhattacharyya, Paromik; Sharma, Tanvi; Yadav, Abhinandan; Lalthafamkimi, Lucy; Ritu,; Swarnkar, Mohit Kumar; Joshi, Robin; Shankar, Ravi; Kumar, Sanjay (Frontiers in Plant Science, 2022)
Malaxis acuminata D. Don [= Crepidium acuminatum (D. Don) Szlach.] is an endangered medicinal orchid of Ashtvarga group of plants in Ayurveda (Indian system of traditional medicine). Using a combination of aromatic cytokinin [meta-Topolin (mT)], plant biostimulant (chitosan), auxin [indole -3-butyric acid (IBA)] and a phenolic elicitor-[phloroglucinol (PG)], plants of M. acuminata were regenerated in vitro for mass multiplication of this prized orchid. The present research reveals the first ever transcriptome of M. acuminata. A total of 43,111 transcripts encoding 23,951 unigenes were assembled de novo from a total of 815.02 million reads obtained from leaf and pseudobulb of in vitro raised M. acuminata. Expression analysis of genes associated with β-sitosterol and eugenol biosynthesis in leaf and pseudobulb provided vital cues for differential accumulation of metabolites in M. acuminata. UPLC confirmed higher amounts of β-sitosterol and eugenol content in leaf as compared to the pseudobulb. Differential expression of transcripts related to starch and sucrose metabolism, plant hormone signal transduction, diterpenoid biosynthesis, phenylalanine metabolism, stilbenoid, diarylheptanoid and gingerol biosynthesis suggested operation of differential metabolic pathways in leaf and pseudobulb. The present research provides valuable information into the biosynthesis of secondary metabolites in M. acuminata, which could be used for advanced metabolite bioprospection using cell suspension culture and bioreactor based approaches. Data also suggested that leaf tissues rather than pseudobulb can be used as an alternate source of bioactive metabolites thereby shifting the need of harvesting the pseudobulb. This will further facilitate in the conservation and sustainable utilization of this highly valued medicinal orchid.